Internationalization of micro, small, and medium-sized enterprises in Ecuador: challenges and opportunities - Tejeda-Aguilera, Mario (2025)
In an increasingly competitive global environment, internationalization has become a vital strategy for micro, small, and medium-sized enterprises (MSMEs) seeking to access new markets and enhance their sustainability. In Ecuador, although MSMEs represent the majority of the business fabric, their participation in international trade remains limited. This study aimed to analyze, through a systematic review of scientific literature published between 2010 and 2024, the main challenges and opportunities faced by these firms in their internationalization processes. Databases such as Scopus, Web of Science, SciELO, and Google Scholar were consulted, applying strict inclusion criteria and using the PRISMA protocol to ensure methodological transparency. The findings reveal internal barriers, including limited access to financing, a lack of managerial training, and low adoption of digital technologies, as well as external obstacles such as high logistics costs, regulatory complexity, and weak institutional coordination. Nevertheless, relevant opportunities were also identified, including trade agreements, growing demand for sustainable and culturally distinctive products, and the use of e-commerce. It is concluded that strengthening business capabilities, ensuring access to specialized financing, designing sector-specific public policies, and improving institutional coordination are key elements for achieving a more effective and inclusive internationalization of Ecuadorian MSMEs.